GREEN ECONOMY DEVELOPMENT AND IMPLEMENTATION TO SUPPORT SUSTAINABLE DEVELOPMENT - Drajat, Dandy Ahmad (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Green Economy Development and Implementation in support of sustainable development. Articles using literature study can be interpreted as a series of activities related to methods of collecting library data, reading, taking notes, and processing research materials. The strategy towards a green economy is carried out through three channels, namely: (i) integral adoption of economic, social and environmental considerations in the planning and implementation of development in various sectors and regions; (ii) environmental quality is maintained as indicated by an improvement in the environmental quality index; and (iii) maintenance of an environmental quality index that is agreed upon, compiled and used as a tool to measure sustainable development.